Statistically Convergent Difference Sequence Spaces of Fuzzy Real Numbers Defined by Orlicz Function: Binod Chandra Tripathy, Stuti Borgohain - Team, Support (Thai Journal of Mathematics, 2013)
The classes of statistically convergent difference sequence spaces of fuzzy real numbers defined by Orlicz functions are introduced. Some properties of these sequence spaces like solidness, symmetricity, convergence-free etc. are studied. We obtain some inclusion relations involving these sequence spaces.